Recent progress in cassava varietal improvement in Indonesia - Poespodarsono, Soemarjo (International Center for Tropical Agriculture, 1998)
In Indonesia, cassava is used mostly for human consumption, while a smaller part is used for animal feed and as raw material in industry. This crop is cultivated in almost all provinces of Indonesia. However, because the amount of rainfall among the regions varies and is not evenly distributed, some regions have a wet climate while others have a dry climate. The type of climate affects the suitability of a particular variety and its productivity.